'Ngondek' Celebration in Variety Shows on Television: A Critical Discourse Analysis - Utami, Dewi; Suwarso, Widha Anistya (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Variety show Ms.Queen on the NET television station March 22, 2022